Rapidly photocurable solid-state poly(ionic liquid) ionogels for thermally robust and flexible electrochromic devices - Poh, Wei Church (2023)
Formation of ionogels through in situ polymerization can effectively improve electrolyte processability; however, the curing process has been slow and oxygen-sensitive. Considering the low oxygen solubility of poly(ionic liquid)s (PILs), in situ polymerized ionogels are designed to realize excellent electrolytes. Herein, two in situ polymerized ionogels (PIL A & PIL B) are formulated, and they can be rapidly photocured within a minute. The ionogels are highly transparent, stretchable, and exhibit excellent physicochemical stability, including thermal, electrochemical, and air stability, allowing them to perform in various conditions. Benefitting from these properties, two high-performance electrochromic devices (ECDs) are assembled, with iron-centered coordination polymer (FeCP) and tungsten oxide (P-WO3 ) electrochromic materials, achieving high color contrast (45.2% and 56.4%), fast response time (1.5/1.9 and 1.7/6.4 s), and excellent cycling endurance (>90% retention over 3000 cycles). Attributed to the thermal robustness of the ionogels, the ECDs can also be operated over a wide temperature range (-20 to 100 °C). With the use of deformable substrates (e.g., ultrathin ITO glass), curved electrochromic eye protector and flexible electrochromic displays are realized, highlighting their potential use in futuristic wearables.